Fungal contamination of ward furnishings and medical equipment used in the treatment and nursing of newborns - Agnieszka Gniadek (Annals of Agricultural and Environmental Medicine, 2020)
Introduction and objective Newborn babies staying on hospital wards are likely to be colonized by microorganisms, including potentially pathogenic fungi. The aim of the study was to assess the mycological purity of hospital wards and medical equipment utilized in the treatment and nursing of newborns.